Adaptive doctors in Australia: preparing tomorrow's doctors for practice in a world destabilised by declining planetary health. Issue 5 (11th April 2022) - Slimings, Claudia; Sisson, Emily; Larson, Connor; Bowles, Devin; Hussain, Rafat
Abstract: Medical professionals need to be equipped with competencies to provide sustainable healthcare and promote planetary health. The aims of this study were to map the presence of planetary health themes in one Australian medical program, develop and pilot a planetary health blended-learning module drawing on constructivism learning theory, and evaluate the effectiveness of the activities. A mixed methods approach was used comprising quantitative mapping of learning outcomes, measurement of pre- and post-intervention planetary health knowledge, and a feedback survey. Mapping revealed little integration of environmental issues across the medical program. Student's knowledge score increased by 2.37 points on average (95% confidence interval 1.66–3.09) (response rate 46%); 84.2% of respondents rated the activities as excellent/good. Since planetary health education is not currently required in Australian medical curricula, there is still little information for local medical educators on how to develop it, therefore studies such as this can provide some preliminary guidance. Supplemental data for this article is available online at https://doi.org/10.1080/13504622.2021.2025343 .